HOW EMERGING ADULTS PRESENT THEMSELVES ON SOCIAL MEDIA: ONLINE SELF-PRESENTATION INFLUENCED BY SELF-ESTEEM, NARCISSISTIC PERSONALITY, AND ONLINE PRIVACY - Paujiatul Arifah; Hera Lestari Mikarsa; Wahyu Rahardjo (Universitas Pendidikan Ganesha, 2023)
Social media is a platform that supports individual online self-presentation activities, especially for users in emerging adulthood. Emerging adulthood is a transitional phase where individual self-identity is being questioned. Many users at that age cannot make their online self-presentation as they should. This research aimed to find out how self-esteem, narcissistic personality, and online privacy can influence the online self-presentation of individuals in emerging adulthood. Participants in this research were 281 active Instagram users and were in the emerging adulthood age range, namely 18-25 years. The data analysis technique used hierarchical regression. The results show that self-esteem and narcissistic personality simultaneously influence online self-presentation, and a stronger influence is found when online privacy is included in the analysis. Narcissistic personality is the variable that most strongly influences online self-presentation of individuals in emerging adulthood. Female participants have a higher level of narcissistic personality than male participants.